Tissue myocardial Doppler echocardiography in the assessment of right ventricular function among patients with pulmonary hypertension of various aetiology - Yu. A. Andreeva; M. A. Saidova; T. V. Martynyuk; V. P. Masenko; I. E. Chazova (Кардиоваскулярная терапия и профилактика)
Aim. To study right ventricular (RV) structure and function, assessed by standard echocardiography (EchoCG), tissue myocardial Doppler (TMD) EchoCG, and natriuretic peptide (NUP) levels, in patients with pulmonary hypertension (PH) of various aetiology. Material and methods. The study included 102 PH patients: 29 with idiopathic PH (IPH), 15 – with PH and pulmonary thromboembolia (PTE), 18 – with PH and systemic scleroderma (SS), 13 – with PH and chronic obstructive pulmonary disease (COPD), 12 – with residual PH. The control group included 21 healthy volunteers. In all participants, standard EchoCG, TMD, measurement of brain and atrial NUP levels were performed. Results. According to the standard EchoCG results, the maximal and minimal heart and pulmonary artery remodelling was observed, respectively, in IPH and COPD. NUP levels correlated with remodelling severity in PH patients. The extent of RV ejection fraction (EF) reduction correlated with the decrease in systolic velocity of tricuspid valve motion. Maximal and minimal systolic RV dysfunction was observed in patients with IPH and COPD, respectively. Although at standard EchoCG, there was no clear evidence of diastolic RV dysfunction, TMD revealed diastolic RB dysfunction in all PH patients. According to TMD results, diastolic RV dysfunction (RVDD) was maximal in IPH individuals. Additionally, TMD demonstrated substantial RVDD, combined with high NUP levels, in patients with PTE and SS. In contrast with standard EchoCG, TMD revealed RVDD in all PH patients. Conclusion. TMD is more effective than standard EchoCG in diagnosing RVDD, associated with elevated NUP levels, in PH patients.